Answer:
-8b^3ax^2
Step-by-step explanation:
Answer:
![\displaystyle m^{\frac{35}{12}}n^{-\frac{28}{15}}=\frac{m^{\frac{35}{12}}}{n^{\frac{28}{15}}}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20m%5E%7B%5Cfrac%7B35%7D%7B12%7D%7Dn%5E%7B-%5Cfrac%7B28%7D%7B15%7D%7D%3D%5Cfrac%7Bm%5E%7B%5Cfrac%7B35%7D%7B12%7D%7D%7D%7Bn%5E%7B%5Cfrac%7B28%7D%7B15%7D%7D%7D)
Step-by-step explanation:
The relevant rule of exponents is ...
(a^b·c^d)^e = a^(be)·c^(de)
Then ...
(m^(5/4)·n^(-4/5))^(7/3) = m^(5/4·7/3)·n^(-4/5·7/3)
= m^(35/12)·n^(-28/15)
__
Since you want positive rational exponents, you can write this as ...
= m^(35/12)/n^(28/15)
Answer:
10.4900
Step-by-step explanation:
pls make a brainliest
Answer:
Original price was $50 x 0.20 = 10
original price $50 - 10 = $40 the sale price before sales tax
Step-by-step explanation:
hopefully it helps